Kijashko-Pikovsky-Rabinovich noise generator: computer simulation and experiment - Anisimov, I.O.; Schur, A.V.; Siversky, T.V. (Вопросы атомной науки и техники, 2003)
Characteristic regimes of Kijashko-Pikovsky-Rabinovich (KPR) noise generator were investigated on the basis of analytic theory and numerical simulation. Previously unknown regimes were found out. Modified circuit of KPR noise generator using the operational amplifiers was developed. Signal waveforms were measured. Several regimes of KPR noise generator predicted by simulation were experimentally verified. Especially the relaxation regimes for large gain factors of the operational amplifier were obtained.